Efficacy and safety of COVID-19 inactivated vaccine: A meta-analysis - Li, Xiaoming; Yang, Xia; Ning, Zong (Frontiers in Medicine, 2022)
Background Inactivated vaccine is one of the primary technology types of Coronavirus Disease 2019 (COVID-19) vaccines, which has wide application in many countries, including mainland China. However, systematic evaluation of the efficacy and safety of COVID-19 inactivated vaccines remains limited. And trust in the vaccine is the key to solving vaccine hesitancy. Methods Various academic databases were searched comprehensively for randomized controlled trials (RCTs) related to COVID-19 inactivated vaccines. The deadline for retrieval was December 2021. Study screening and data extraction were according to inclusive and exclusive criteria. Statistical analyses were performed using RevMan software 5.3 version and STATA software 16.0 version. Results Eight studies with 79,334 subjects were included of which 48,123 had received two doses of COVID-19 inactivated vaccines, and 31,211 had received two doses of placebo. The results of the meta-analysis showed that: in terms of effectiveness evaluation, two doses of COVID-19 inactivated vaccines decreased the symptomatic infection [relative risk (RR) = 0.23, 95% confidence interval (CI) (0.18,0.30), P < 0.00001], asymptomatic infection [RR = 0.48, 95%CI (0.32, 0.74), P = 0.0008], total infection [RR = 0.32, 95%CI (0.24, 0.41), P < 0.00001] and hospitalization [RR = 0.06, 95%CI (0.01, 0.27), P = 0.0002] for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) significantly. In terms of safety assessment, two doses of COVID-19 inactivated vaccines also caused more adverse events. After two inoculations, total adverse events and systemic adverse events increased significantly [total adverse events RR = 1.14, 95%CI (1.08, 1.21), P < 0.00001; systemic adverse events RR = 1.22, 95%CI (1.09, 1.35), P = 0.0002]. The most common adverse event was pain at the injection site. Almost all local adverse reactions consisted of these events. The incidence of pain at the injection site was related to adjuvants. Using aluminum hydroxide as an adjuvant increased local pain significantly [RR = 1.97, 95%CI (1.52, 2.55), P < 0.00001]. Two doses COVID-19 inactivated vaccines did not increase serious adverse events [RR = 0.71, 95%CI (0.57, 0.90), P = 0.004]. Conclusion Two doses of inactivated COVID-19 vaccines in people over 18 years of age effectively prevented SARS-CoV-2 infection and its associated hospitalizations. Short-term, mild to moderate adverse reactions had occurred, but serious adverse events were rare. No placebo or vaccine-related deaths had been reported. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier: 42021291250.